STRATEGI HUMAS DALAM MEMPERTAHANKAN CITRA POSITIF PERUSAHAAN (Studi kasus pada Coffeeshop PT Stasiun Kopi Solo Balapan): Studi kasus pada Coffeeshop PT Stasiun Kopi Solo Balapan - Septiyani, Amita Widi; Sarjono, Herning Suryo; Sihabuddin, Sihabuddin (Solidaritas, 2024)
Research with the title Public Relations Strategy in Maintaining the Company's Positive Image (Case study at Coffeshop PT Stasiun Kopi Solo Balapan) is a study that raises about Public Relations Strategy in maintaining the company's positive image, aims to find out and describe the strategies used by Coffeshop PT Stasiun Kopi Solo Balapan. The theory (Cutlip, Center and Broom, 2005) used in this study. In this study, the method used is a qualitative descriptive approach, so that this research describes the actual situation, trying to reveal a problem as it is so that it reveals facts about public relations strategies in maintaining a positive image of the company. In collecting qualitative data, the author processes information obtained from primary data sources that describe the data, namely with explanatory descriptions derived from the results of field interviews and field observations conducted in connection with the Coffeshop PT Solo Balapan Coffee Station. The results showed that the Public Relations of PT Stasiun Kopi Solo Balapan Coffeshop in an effort to improve the positive image of the company was seen to have carried out a situation analysis, planning and programming, implementing, and evaluating the program. Positive image building is done by presenting very interesting events every month. Researchers suggest to the PR to expand social media promotions, as well as events and good relations with the mass media so as to build a good image for the company. Keywords: Public Relations Strategy, Coffeshop PT Solo Balapan Coffee Station, Positive Image